1980
DOI: 10.7164/antibiotics.33.13
|View full text |Cite
|
Sign up to set email alerts
|

Studies on new phosphonic acid antibiotics. I. FR-900098, isolation and characterization.

Abstract: A strain of Streptomyces, isolated from a soil sample and identified as Streptomyces rubelloinurinus sp. nov., has been found to produce FR-900098, an interesting new antibiotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 15 publications
1
74
0
Order By: Relevance
“…Blind PCR screening of this library identified 403 putative phosphonate producers. Subsequent draft genome sequencing of all candidate strains confirmed the presence of pepM in 278 strains, including 244 from the NRRL collection; 30 from our laboratory collection; and four additional strains specifically added to the study because of their known ability to produce phosphonothrixin (26), FR-900098 (27), and fosmidomycin (28) (SI Appendix, Table S1). The majority (87%) of the pepM + strains are Streptomyces, with the remainder scattered among 24 genera, a distribution that mirrors the composition of the strain collection.…”
Section: Resultsmentioning
confidence: 99%
“…Blind PCR screening of this library identified 403 putative phosphonate producers. Subsequent draft genome sequencing of all candidate strains confirmed the presence of pepM in 278 strains, including 244 from the NRRL collection; 30 from our laboratory collection; and four additional strains specifically added to the study because of their known ability to produce phosphonothrixin (26), FR-900098 (27), and fosmidomycin (28) (SI Appendix, Table S1). The majority (87%) of the pepM + strains are Streptomyces, with the remainder scattered among 24 genera, a distribution that mirrors the composition of the strain collection.…”
Section: Resultsmentioning
confidence: 99%
“…Before use, the lactones of MV and MVA were converted to their open acid forms. Fos (Okuhara et al, 1980) was made available by Robert J. Eilers (Monsanto, St. Louis, MO). The peptidomimetic protein geranylgeranylation inhibitor GGti-2133 (Vasudevan et al, 1999) was purchased from Calbiochem (Merck).…”
Section: Chemicalsmentioning
confidence: 99%
“…We have succeeded in the first cloning and overexpression of the gene (dxr, formerly yaeM) encoding the DXP reductoisomerase from E. coli and have shown that the recombinant enzyme catalyzed the formation of MEP from DXP in a single step in the presence of both NADPH and a divalent cation, such as Mn 2Ï© , Mg 2Ï© , or Co 2Ï© (10,11). Additionally, we have demonstrated that the enzyme activity is strongly and specifically inhibited by fosmidomycin (FR-31564) (12), an antibiotic possessing the formyl and phosphonate functions in the molecule (13)(14)(15)(16) (Fig. 1).…”
mentioning
confidence: 94%
“…Thus, it is evident that the analyses of these mutants provide important information on critical amino acid residues in catalysis and/or structural integrity. DNA sequencing analysis revealed the point mutations of the amino acids, Gly 14 to Asp 14 and from Glu 231 to Lys 231 in the E. coli dxr-deficient mutants. These amino acid residues, Gly and Glu, were found in all the DXP reductoisomerase sequences from nine organisms (Fig.…”
mentioning
confidence: 99%